First report of bovine trypanosomiasis in the Kashmir Valley: Therapeutic approach (VETERINARIA, 2025)
Trypanosomiasis is a protozoan disease of major economic importance in livestock worldwide, but it has not been documented in the high-altitude, temperate climate of Kashmir, India. This article reports the first confirmed case of trypanosomiasis in non-descript cattle from the Kashmir Valley. A two-year old female non-descript cow in the first trimester of pregnancy was presented with a history of weakness, infestation of ticks, anorexia, haematochezia, unilateral epistaxis and pica to the Division of Veterinary Clinical complex, FVSc & AH for the treatment. Clinical examination revealed hypothermia, white mucous membrane, enlarged prescapular lymph nodes, tachycardia, respiratory distress and hyper salivation. Haematological analysis revealed very low haemoglobin content and on blood smear examination Trypanosoma evansi organisms were identified which was further confirmed through presence of Trypanosoma evansi tryps in the lymph node aspirate. Blood transfusion was done with whole blood immediately and then Inj. diminazene aceturate @ 5 mg/kg intramuscularly was given which was repeated on 5th day. After 5 days haemantinics were also given. The animal showed clear signs of recovery after blood transfusion. This constitutes the first case of surra in the Kashmir Valley, highlighting the parasite’s expansion into the temperate region of the country and marking a critical observation for veterinary practitioners in the region. Future work is needed to identify the vector and possible reservoirs to prevent the spread of the disease.
Keywords: Trypanosomiasis; surra; Trypanosoma evansi